2019
DOI: 10.24843/jvas.2019.v02.i02.p03
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Bali Cattle as a Bull in Nusa Penida Island-Bali Based on Its Performance and Breeding Value

Abstract: Selection program applied to improve the animal genetic potential.  This program can be carried out based on the performance and breeding values ??of the economic trait of each individual.  The research was carried out for 5 month (from May until September 2018).  The purpose of this study was to find out the superior Bali bull by determining of chest girth male Bali cattle. This study used purposive random sampling method. The number of male Bali cattle with incisor of I0,I1,I2 used in this study were 147,29,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Code 5 goats can be used as male candidates to improve the genetic quality of the goat population in Jembrana district. Warmadewi et al [6] who found that chest circumference has a closer relationship with body weight compared to body length and shoulder height. Therefore, selection to improve the genetic quality of goats is more effective on chest circumference compared to selection on body length and shoulder height.…”
Section: Resultsmentioning
confidence: 98%
“…Code 5 goats can be used as male candidates to improve the genetic quality of the goat population in Jembrana district. Warmadewi et al [6] who found that chest circumference has a closer relationship with body weight compared to body length and shoulder height. Therefore, selection to improve the genetic quality of goats is more effective on chest circumference compared to selection on body length and shoulder height.…”
Section: Resultsmentioning
confidence: 98%
“…Heritability of body length in cattle is around 0.34-0.51 and chest girth is around 0.27 to 0.47 (Kamprasert et al, 2019). Heritability at the withers height of Bali cattle is 0.6 (Warmadewi et al, 2017) (Nuraini et al, 2018). Therefore, the breeding program for Buffalo in Indonesia must prioritize frame size and carcass percentage.…”
Section: Resultsmentioning
confidence: 99%
“…The most prominent advantage of Bali cattle is high fertility [1,2] ; high reproduction; sufficiently good adaptability to new environments, especially the ability to adapt to low quality feed [18] high percentage of carcass and good quality of meat [14] . Based on these advantages, Bali cattle are very feasible to be improved and developed, both in terms of genetic quality and population [20] . In addition, the government has designated Bali cattle as the main local beef producer to support the beef self-sufficiency program in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Good genetic quality will not be expressed if it is not supported by an optimal environment/feed. Conversely, if the genetic quality is bad/not good, the optimal environment/feed will not provide maximum performance [20] . The action needed to improve the genetic quality of Bali cows is to select and mate within the Balinese cattle breed, so that the purity of the calves can be maintained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation